Plan Logístico de Distribución y Transporte para Productos alimenticios de la Empresa Ecoal Chimborazo S.A en la ciudad de Riobamba. - Chiliquinga Guerra, Dayana Andrea (2025)
This research project aimed to develop a logistics plan for the distribution and transportation of food products from the company Ecoal Chimborazo S.A. in the city of Riobamba to solve delivery delays. Surveys were carried out on employees and their attention to adequately planning product delivery times and routes. In addition, the data provided by the drivers was analyzed, showing that 83% of deliveries were completed on time and 71% met compliance requirements. These indicators reflect the need to improve delivery performance to ensure the company's long-term competitiveness. The proposed solution was to develop a logistics plan using the open-source tool VRP Spreadsheet Solver, which allowed for the simulation of optimal delivery routes and ensured that orders would be delivered as agreed with customers. The results of this plan showed that the software was able to complete all deliveries on the scheduled day and optimized the use of the fleet, providing effective solutions to the problem identified in the distribution and transportation process.